Trust in health care credence goods: Experimental evidence on framing and subject pool effects - Silvia Angerer; Daniela Glätzle-Rützler; Christian Waibel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Credence goods markets are characterized by asymmetric information concerning the needed and/or provided quality between experts and consumers. The functioning of the market heavily relies on trust on the side of the consumer as well as trustworthiness on the side of the expert. However, a great amount of empirical and experimental papers document for a range of different credence goods markets the existence of over-, undertreatment, and overcharging. In this paper, we study two determinants of trust and trustworthiness in experimental credence goods markets, namely the effect of a health frame (versus a neutral frame) as well as the identity of the expert (being either a standard student subject or a prospective physician). Our results reveal that the identity in combination with a health frame has a significant impact on the level of trust shown by a higher willingness of consumers (patients) to enter the market. Trustworthiness, as measured by the provision and charging behavior of experts, however, is not significantly influenced by the health care framing, nor by the subject pool.
Keywords: C91; D82; I11; 330; Health care economics; trust; fraud; framing effects; experts; credence goods; undertreatment; overcharging; laboratory experiment